Macht, Praxis, Sinn: Anmerkungen zur empirischen Sozialforschung in Afrika - Schiefer, U. (Peripherie, 1995)
Social research is always influenced essentially by the society, wherein it takes place. However, this fact has special consequences in respect of social research in Africa. Social research in Africa is accompagnied by difficulties, that have been so far ignored in social science literature. The author illustrates some of these problems in describing his own research-project in Guinea-Bissau. Beginning with the recruitment of adequat staff, trying to convince the local authorities to cooperate and going on to keep the research equipment together, all these tasks require an understanding of the local society even before research is started. However, the reliability of any of the results is extremely dependend on solving these problems.